Retraction Note: Exploring the potential effect of COVID-19 on an endangered great ape - Fernando Colchero; Winnie Eckardt; Tara Stoinski (Scientific Reports, 2022)
Abstract This Article has been retracted; the Retraction Note is available at: https://doi.org/10.1038/s41598-021-00061-8 .